2019
DOI: 10.1186/s13567-019-0695-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of neuromedin B and its receptor in the innate immune responses against influenza A virus infection in vitro and in vivo

Abstract: The peptide neuromedin B (NMB) and its receptor (NMBR) represent a system (NMB/NMBR) of neuromodulation. Here, it was demonstrated that the expression of NMBR in cells or murine lung tissues was clearly upregulated in response to H1N1/PR8 influenza A virus infection. Furthermore, the in vitro and in vivo activities of NMB/NMBR during PR8 infection were investigated. It was observed that A549 cells lacking endogenous NMBR were more susceptible to virus infection than control cells, as evidenced by the increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Many reports about the possible role of NMB in tumor cell infiltration have emerged in recent years. Yang reported that NMB and NMBR may be involved in the spontaneous actin polarization of transformed CD8 T cells [22]. However, the correlation analysis of NMB expression and TILs has not been reported in GBM patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports about the possible role of NMB in tumor cell infiltration have emerged in recent years. Yang reported that NMB and NMBR may be involved in the spontaneous actin polarization of transformed CD8 T cells [22]. However, the correlation analysis of NMB expression and TILs has not been reported in GBM patients.…”
Section: Discussionmentioning
confidence: 99%
“…The NMBR antagonist PD168368 inhibited the growth of MDA-MB-231 breast cancer cells by inducing cell cycle arrest and apoptosis [21]. Yang reported that BIM-23127, an NMBR antagonist, could potentially inhibit cellular proliferation [22] and induce the death of the medulloblastoma cell line DAOY [23].…”
Section: Discussionmentioning
confidence: 99%
“… 62 Several studies have shown that NMBR plays an innate immune defense role against respiratory viral infection by enhancing IFN-alpha and reducing the expression of IL-6. 63 Females have been shown to have greater Type I IFN responses and are less susceptible to viral infections than males. 64 We reasonably infer that any abnormality or polymorphic alterations in the NMBR gene may have a higher impact on males.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropeptide S ( NPS ) and its receptor ( NPSR1 ) are central to sleep regulation and are linked to the control of feeding behaviour [24, 25, 26]. Neuromedin B Receptor ( NMBR ) has been linked with both hormonal regulation and immunity control [27, 28]. Somatostatin Receptor 4 ( SSTR4 ) plays a role in hormonal regulation and in stress responses [29].…”
Section: Introductionmentioning
confidence: 99%